Non-invasive Methods for Energy and Seismic Retrofit in Historical Building in Italy - Negro, Elisabetta; D'Amato, Michele; Cardinale, Nicola (Frontiers in Built Environment, 2019)
Italian historical buildings do not respect often standard requirements established by National regulations, so that they need of an energy requalification. In addition, commonly the adopted provisions do not belong to an integral design approach in which different aspects, such as architectonic, energetic, and structural should be together considered for obtaining a total building rehabilitation. This work mainly addresses to the application of non-invasive methods for energy retrofitting of historical buildings in Italy. In particular, an energy audit protocol is studied and applied to a case study, consisting on an ancient masonry building located within the historical center of “Sassi of Matera,” recognized as UNESCO site since 1993. In the paper some energy efficiency measures are considered, by examining also alternative interventions with respect to the classical ones, by applying innovative and sustainable materials, fashionable as well from a structural point of view. This proposal, to be investigated more in detail in future, responds to the criteria of non-invasiveness for preserving the cultural heritage identity, and simultaneously improving the energy and the structural response.